Instrumentos de avaliação da função sexual feminina e formação profissional fisioterapeuta em relação à sexualidade humana - Saldanha, Maria Elisabete Salina (2017)
Background and Aims: Currently, sexuality is considered an aspect that affects to quality of humans life, thus it is necessary to evaluate and intervene in those related to sexual function. In this context, two studies were developed. In the first, the aim was to verify the methodological quality of validation of the instruments of sexual function evaluation available in Portuguese/ Brazil literature. The second study aimed to evaluate the knowledge, comfort and attitudes of physiotherapy students in situations involving questions related to human sexual function. Methods: The first study sought after instruments in scientific bases for the evaluation of sexual function. The 11 instruments, described in 12 studies, were analyzed using Consensus-based Standards for the selection of health Measurement Instruments (COSMIN). The second study evaluated the response of 510 physiotherapy students based on scale of knowledge, comfort and attitudes of physiotherapy academics regarding human sexuality (ECCAFS). Results: The results of the first study demonstrate failures in the process of testing properties of validated questionnaires in Portuguese / Brazil. The second study verified that the period of university formation, age, gender and social class were relevant in the knowledge, comfort or attitude of Physical Therapy academics on issues related to Human sexuality. Conclusion: It is noted that questionnaires evaluated in the first study had failures in measurement properties tests. The physiotherapist's knowledge, comfort, discomfort and attitude may vary concerning the stage of training, gender, social class and age.